Effect of Current Ratio and Debt to Equity on Price to Book Value with Return on Equity as an Intervening Variable in the Consumer Goods Industry Sector in Companies Listed on the IDX in the Period 2016-2018 - Yuliani; Yusuf Ronny Edward; Enda Novianty Simorangkir (Kusuma Negara Business School, 2020)
This study aims to test and analyze the effect of Current Ratio (CR) and Debt to Equity (DER) on Price to Book Value (PBV) through the Return on Equity (ROE) of the Consumer Goods Industry Sector in companies listed on the IDX for the 2016-2018 period. The research method used in this research is quantitative research methods. The nature of the research used in this study is a causal relationship. The population in this study were 33 companies consisting of 3 years. The selection of research samples using purposive sampling technique, namely sampling with certain criteria so that the number of samples taken was 99 samples. Data analysis method used in this research is path analysis, determination coefficient, Direct Effect and Indirect Effect test. The results showed that Current Ratio (CR) and Debt to Equity (DER) to Price to Book Value (PBV) through Return on Equity (ROE). Current Ratio (CR) had no effect on Price to Book Value (PBV), Debt to Equity (DER) affects Price to Book Value (PBV), Current Ratio (CR) and Debt to Equity (DER) affect Return on Equity (ROE), Current Ratio (CR) has no effect on Price to Book Value (PBV) through Return on Equity (ROE) as an Intervening variable and Debt to Equity (DER) affects the Price to Book Value (PBV) through Return on Equity (ROE) as an Intervening variable.